The first dog - Brett, Jan, 1949- (San Diego : Harcourt Brace Jovanovich, 1988)
Kip the Cave Boy and Paleowolf each face hunger and danger on a journey in Paleolithic times; when they decide to join forces and help one another, Paleowolf becomes the first dog.
SSLI Best Book
Child Study Children's Book Committee
School Library Journal
2.8
K-3
Keywords: Dogs -- Fiction; Prehistoric animals -- Fiction; Man, Prehistoric -- Fiction; Dogs -- Fiction; Prehistoric animals -- Fiction; Man, Prehistoric -- Fiction